Development of a machine learning model to determine the behavior of frost in the Bogotá Savannah - Castillo Méndez, Robinson
Gross motor skills are a fundamental resource in early childhood care, which requires planning in the activities to be developed with infants who attend the service units (UDS) belonging to the Colombian Institute of Family Welfare (ICBF) in the municipality of Fusagasugá-Colombia. With the implementation of a custom-designed mobile application in a medium that lacked this resource, it turns out to be invaluable not only as an assistance tool, but also as a support for the service units of the region, helping teachers and community mothers to plan their daily tasks. The design of the application is based on the Mobile-D methodology, characterized by being flexible and adaptable to the changing needs of users, providing rapid development and iteration with them. The results show that the application facilitates the management of pedagogical resources and registration forms of the activities that must be permanently completed. The design, development and execution of the pedagogical resources managed through the application facilitate academic and administrative processes that were previously carried out manually. According to the conclusions, the mobile application met the requirements using tools such as React Native, Sequelize and Express, facilitating its planning and execution. The lessons learned highlight the importance of involving users in the planning and the appropriate choice of tools to increase the accessibility and reach of the application.